Aplikasi Nilai Objektivitas pada Konsep Desain Interior Kantor - Ulli Aulia Ruki (Bina Nusantara University, 2013)
Now days, planning an office was more than preparing desk and chair, it needed numbers of important decisions to be considerered, such as, where and how did the workers want to work?, What kinds of workspace that supported employee’s activities and how much did the office use the new technologies. Article would acknowledge the designer about nine objectives that needed to be known before planning an office and six crucial choices about the place and way of working. Moreover, the designer would have the same frame of working with managers to create the success of office facilities. Researcher used library research to compile data.It is concluded that manager and designer needs to prioritize and discusses detail such as location, use, layout, appearance, filling and standardization concept to make an office efficient and meet the employess needs.